PENGEMBANGAN MODUL PENDIDIKAN PERTAMA PADA ANAK BERLANDASKAN NILAI MORAL DAN ETIKA RELIGIUS - Ari Muhammad Rahman ari; Sri Rahayu Pudjiastuti; Mohamad Sutisna (Epistemic: Jurnal Ilmiah Pendidikan, 2026)
This study addresses the limited availability of practical and contextual learning resources for mothers in Islamic nonformal education settings to foster moral and religious ethics in early childhood. Although majelis taklim has strong potential as a community-based educational space, its role in supporting family-based moral education is often not accompanied by structured pedagogical guidance. This research aims to develop a community-based moral education module for early childhood in Majelis Taklim Ar-Rahmaniyyah, Sukabumi. The study employed a research and development design consisting of three stages: preliminary study, product development, and product testing and finalization. Data were collected through observation, interviews, questionnaires, and documentation. The product was validated by material and media experts, followed by a limited trial with 10 participants and a field trial with 20 participants using a one-group pretest-posttest design. The findings show that the module is valid, practical, and effective. It improved mothers’ ability to guide children’s moral and religious behavior through habituation, modeling, dialogue, and reinforcement. The study contributes to the literature by demonstrating that community-based Islamic nonformal education can strengthen family moral education when supported by a contextual and operational module.